PENGARUH MOTIVASI DAN METODE MENGAJAR TERHADAP PRESTASI MATA KULIAH HADITS MAHASISWA IAIN PADANGSIDIMPUAN - Hj. Tatta Herawati Daulae (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
This study has been done to get the overview of learning methods used by the lectures and motivation given by lectures, and the influence to students’ learning achievement in Hadist at IAIN Padangsidimpuan. The result shows that the lecturer’s motivation and learning methods used in learning Hadits is in the middle category. Then, students’ achievement in learning Hadits is good (on the average 76.75 : B). Based on the result, it is shown that the motivation from lecturer and learning method used give the significant contribution to the students’ achievement in learning Hadist.